PELAKSANAAN KEPUTUSAN PEMERINTAH MENGENAI PERIZINAN RITEL ALFAMART DAN INDOMARET DI KOTA PEKANBARU TAHUN 2012-2013 - Febra Putri; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of Government Decision regarding Licensing and Retail Alfamart Indomaret in Pekanbaru City Year 2012-2013. And the purpose of this study was to determine the Implementation of Decisions Retail Licensing Mayor of Pekanbaru on Alfamart and Indomaret Year 2012-2013 and to find out why the decision is not complied with by the Mayor of Pekanbaru Indomaret.peneltian Alfamart and the use of qualitative research methods by incorporating quantitative descriptive data assessment. By using the key information resources. Based on the research that has been conducted based on the concept and theory researchers found that the implementation of Government Decree on Licensing and Retail Alfamart Indomaret in Pekanbaru City Year 2012-2013 has not been going well as expected in Pekanbaru mayor's decision. It can be seen still occur Alfamart and Indomaret operating but has not had a license.Keywords : Implementation, Retail, Licensing, Government Decision